Cognitive empathy in conflict situations - Florian Gauer; Christoph Kuzmics (Bielefeld University, Center for Mathematical Economics (IMW), 2016)
Two individuals are involved in a conflict situation in which preferences are ex ante uncertain. While they eventually learn their own preferences, they have to pay a small cost if they want to learn their opponent's preferences. We show that, for sufficiently small positive costs of information acquisition, in any Bayesian Nash equilibrium of the resulting game of incomplete information the probability of getting informed about the opponent's preferences is bounded away from zero and one.
urn:nbn:de:0070-pub-29003860
Keywords: C72; C73; D03; D74; D82; D83; 330; Incomplete Information; Information Acquisition; Theory of Mind; Conflict; Imperfect Empathy